Enhancing Architectural Learning: Integrating Building Technology with Innovative Pedagogy - Samudro, Harida; Bahar, Moh. Arsyad; Firmansyah, Aldrin Yusuf; Yulianto; Darma, Muhammad Akbar Setia (Edukasi, 2025)
Architectural education is essential in shaping the future of the profession, and as technology evolves, integrating building technology into design studios becomes crucial. This study evaluates the integration of building technology within architectural design studio learning, with a focus on pedagogical effectiveness, curriculum alignment, and student engagement. Conducted within the Department of Architecture at Maulana Malik Ibrahim State Islamic University in Malang, the research involved 100 third-year undergraduate architecture students in a studio-based educational setting. Using a mixed-methods approach, including structured student surveys and literature-based benchmarking, the research assesses how well design studios incorporate technical knowledge, foster interactive learning, and support applied problem-solving. The findings reveal that while 62.6% of pedagogical components meet the desired benchmarks, significant gaps remain in the application of interactive and game-based learning methods. Collaborative learning scores were strong, ranging from 69.6% to 80.6%, but gamification and hands-on activities had low participation rates of 27% to 44.8%. Students showed solid analytical skills at 63.8% but struggled with innovative design, scoring only 59%. To improve the program, enhancements in experiential learning, course alignment with studio practice, and creative assessments are needed to better prepare graduates for modern architectural challenges.